Depiction of Brahma on the Uttaranga - Temples of India Project Team (Jio Institute, 2024)
On the left of the uttaranga (entablature) above the lintel of the garbhagriha (sanctum sanctorum), Brahma is depicted with three faces and four arms. His upper hands carry a shruka (a sacrificial spoon) and a pustaka (manuscript), while his lower hands hold a kamandalu (water carrier or pot) and display varadaksha (a hand held in the boon-giving gesture, with a rosary in it).